Multimodal regulation of the osteoclastogenesis process by secreted group IIA phospholipase A2 - Mangini, Maria; D’Angelo, Rosa; Vinciguerra, Caterina; Payré, Christine; Lambeau, Gérard; Balestrieri, Barbara; Charles, Julia F.; Mariggiò, Stefania (Frontiers in Cell and Developmental Biology, 2022)
Increasing evidence points to the involvement of group IIA secreted phospholipase A2 (sPLA2-IIA) in pathologies characterized by abnormal osteoclast bone-resorption activity. Here, the role of this moonlighting protein has been deepened in the osteoclastogenesis process driven by the RANKL cytokine in RAW264.7 macrophages and bone-marrow derived precursor cells from BALB/cJ mice. Inhibitors with distinct selectivity toward sPLA2-IIA activities and recombinant sPLA2-IIA (wild-type or catalytically inactive forms, full-length or partial protein sequences) were instrumental to dissect out sPLA2-IIA function, in conjunction with reduction of sPLA2-IIA expression using small-interfering-RNAs and precursor cells from Pla2g2a knock-out mice. The reported data indicate sPLA2-IIA participation in murine osteoclast maturation, control of syncytium formation and resorbing activity, by mechanisms that may be both catalytically dependent and independent. Of note, these studies provide a more complete understanding of the still enigmatic osteoclast multinucleation process, a crucial step for bone-resorbing activity, uncovering the role of sPLA2-IIA interaction with a still unidentified receptor to regulate osteoclast fusion through p38 SAPK activation. This could pave the way for the design of specific inhibitors of sPLA2-IIA binding to interacting partners implicated in osteoclast syncytium formation.